(3CMGOjK efJbGg ef GdZjdGfjGJs - (3CMeO Hf EHQGgje Hf fUQ Gddg Hf CMeO GdMfHdis; (3CHh HcQ eMeO Hf YHO Gddg Hf EHQGgje GdTGaYj,J (B354 (3g` s
(3ChdgG (B:s
(3gPg GMGOjK efJbGg ef GdfUa GdKGfi ef cJGH GdZjdGfjGJ GNHQfG HgG TjNfG eaJi GdeSdejf CHh GdHQcGJ CMeO YR GdOjf s
(3BNQgG (B:s
(3cedJ GdGMGOjK GdefJbGg ef GdZjdGfjGJ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B7s
(3GdfSNI HgG MhGTs
(3gPg GdGMGOjK efJbGg ef GdfUa GdKGfi ef GdZjdGfjGJs
(3Ydjg SeGY GdcGJH hLeGYI Ydi GdTjN CMeO Hf GHQGgje hNWg eUMM Ydi SeGYg hSeGYge Ydjg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs